PENGARUH MOTIVASI KERJA TERHADAP KUALITAS PELAYANAN DIKANTOR KECAMATAN MAPPAKASUNGGU KABUPATEN TAKALAR - Roy Roy; Lukman Hakim; Nurbiah Tahir (JPPM: Journal of Public Policy and Management, 2020)
This study purposed to find out and analyze the effect of work motivation on service quality in  Mappakasunggu District office of Takalar Regency. This study  used descriptive research by using quantitative methods and approaches that described work motivation towards service quality in the District Office of Mappakasunggu, Takalar Regency, as many as 77 people. Sampling technique   used simple random sampling.  The statistical analysis of the coffisien model table, explaining the magnitude of the correlation or relationship (R) value of 0.590.  The influence of the independent variable or work motivation (X) on the dependent variable of service quality (Y) shown by the standard coffisien of 0.5 or 59% based on these results it could be said that the influence of the independent variable or work motivation (X) on the variable the dependent quality of service (Y) in the Mappakasunggu District Office of Takalar Regency was 0.5, or  59%.